Hsa_circ_0063329 inhibits prostate cancer growth and metastasis by modulating the miR-605-5p/tgif2 axis. Issue 9 (3rd May 2023) - Lv, Daojun; Cen, Shengren; Yang, Shuxin; Zou, Zihao; Zhong, Jianfeng; Pan, Zhaojun; Deng, Nan; Li, Yubin; Wu, Kaihui; Wang, Jiamin; Liu, Ping
ABSTRACT: Circular RNAs play crucial regulatory roles in the progression of various cancers. Nevertheless, the underlying mechanisms of circRNAs in prostate cancer (PCa) proliferation and metastasis remain largely uncertain. Here, we performed circRNA microarray analyses to identify differentially expressed circRNAs in a normal prostate epithelial cell line and PCa cell lines. We found that hsa_circ_0063329 was significantly downregulated in PCa. A series of in vitro and in vivo functional assays showed that overexpression of hsa_circ_0063329 inhibits PCa cell progression, while silencing of hsa_circ_0063329 achieved the opposite effects. Mechanistically, bioinformatics analysis, RNA pulldown, RNA-seq and dual-luciferase reporter assays demonstrated that hsa_circ_0063329 exerts its effect by sponging miR-605-5p to derepress TG-interacting factor 2 (TGIF2) and inactivate the TGF-β pathway. In conclusion, hsa_circ_0063329 inhibits the proliferation and metastasis of PCa via modulation of the miR-605-5p/TGIF2 axis, and targeting hsa_circ_0063329 may provide a promising treatment strategy for aggressive PCa.